Effectiveness of distributing pocket cards in improving the behavior, attitude, and knowledge regarding proper medication use among junior high school students in Japan - Sakai, Chihiro; Iguchi, Kazuhiro; Tachi, Tomoya; Noguchi, Yoshihiro; Hisamatsu, Aki; Katsuno, Shingo; Teramachi, Hitomi (Frontiers in Public Health, 2024)
Objective This study aimed to explore the effectiveness of distributing pocket cards with summaries of key information on appropriate medication usage after the implementation of a structured school-based medication education program for junior high school students in Japan. Methods A total of 227 3rd-grade high school students participated in the intervention. Students who received the program without the provision of pocket cards in 2022 were included in the comparison group, and students who took the program with the provision of pocket cards in 2023 were included in the intervention group. After propensity score matching, the final sample of N = 116 comprised n = 58 comparison group participants and n = 58 intervention group participants. Questionnaires were administered at baseline, end-of-class, and 3-month follow-up to assess the changes in behavior, attitude, and knowledge scores. Results The matched intervention group showed significantly lower scores at the 3-month follow-up than the matched comparison group. The results of the multiple linear regression analysis showed that for both groups, only the attitude scores were significantly correlated with the behavior scores. In addition, regardless of the baseline scores, the matched intervention group demonstrated smaller or negative changes in scores at the 3-month follow-up. Conclusion Overall, the results of this study did not support the effectiveness of distributing pocket cards after in-class intervention. However, the usefulness of medication education intervention was confirmed. These results emphasize the need to explore other supplemental teaching tools to further enhance the impact of structured medication education programs.